Comparison of tumor‐informed and tumor‐naïve sequencing assays for ctDNA detection in breast cancer - Angela Santonja; Wendy N Cooper; Matthew D Eldridge; Paul A W Edwards; James A Morris; Abigail R Edwards; Hui Zhao; Katrin Heider; Dominique‐Laurent Couturier; Aadhitthya Vijayaraghavan; Paulius Mennea; Emma‐Jane Ditter; et al. (EMBO Molecular Medicine)
Abstract Analysis of circulating tumor DNA (ctDNA) to monitor cancer dynamics and detect minimal residual disease has been an area of increasing interest. Multiple methods have been proposed but few studies have compared the performance of different approaches. Here, we compare detection of ctDNA in serial plasma samples from patients with breast cancer using different tumor‐informed and tumor‐naïve assays designed to detect structural variants (SVs), single nucleotide variants (SNVs), and/or somatic copy‐number aberrations, by multiplex PCR, hybrid capture, and different depths of whole‐genome sequencing. Our results demonstrate that the ctDNA dynamics and allele fractions (AFs) were highly concordant when analyzing the same patient samples using different assays. Tumor‐informed assays showed the highest sensitivity for detection of ctDNA at low concentrations. Hybrid capture sequencing targeting between 1,347 and 7,491 tumor‐identified mutations at high depth was the most sensitive assay, detecting ctDNA down to an AF of 0.00024% (2.4 parts per million, ppm). Multiplex PCR targeting 21–47 tumor‐identified SVs per patient detected ctDNA down to 0.00047% AF (4.7 ppm) and has potential as a clinical assay.